Socio-economic Development of Ukraine: problems and solutions (for example Donetsk) - Lukyanchenko, Oleksandr (Skhid, 2013)
In this article the example of Donetsk shows the state and outlined the ways socio-economic development of cities in Ukraine. Argued the need for scientific and national activities aimed at the development of integration policies in local development of the basic principles of the Leipzig Charter for sustainable European city. Under this policy it offers to develop local and regional coordination, whose purpose is to achieve an equal partnership between city and countryside, between small, medium and large cities within the urban and metropolitan regions